Per imitare gli antichi - Paolo Tabacchini (Firenze University Press, 2019)
The article focuses on the role of the Orti Oricellari's Academy in the contruction of the intellectual and political consciousness of the florentine poet of Renaissance Luigi Alamanni. In particular, the paper highlights the importance of two relevant personalities of the accademy: Niccolò Machiavelli and Gian Giorgio Trissino. The biographical informations are put into the cultural and historical context of the period.